Analisis Jenis Tindak Tutur Lokusi pada Teks Cerita Novel Sejarah dalam Buku Bahasa Indonesia Kelas XII Kurikulum 2013 - Ahmad Mirza Aufa; Diah Ayu Wijayanti; Darojatin Mansuriniati; Agista Nurul Inayyah; Anjar Jati Kusuma; Nisrina Najwa Ahmat; Asep Purwo Yudi Utomo (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2024)
Every day, humans are involved in communication using language. During the communication process, everyone in language is always related to factors that affect the smoothness of communication. Communication can never be separated from the name of speech acts, and to state something is called locutionary speech acts. The purpose of this study is to investigate the various locutionary speech acts contained in the narrative excerpts of historical novels contained in Indonesian language textbooks intended for Class XII Curriculum 2013. The research method used is a descriptive approach with qualitative analysis. The data used are narrative excerpts of historical novels from Indonesian language textbooks intended for grade XII students. Among the identified locutionary speech acts, statement speech acts are the most frequently used, with command speech acts and question speech acts also present. Through this research, a deeper understanding of the use of locutionary speech acts in narrative excerpts of historical novels contained in Indonesian language textbooks for class XII of the 2013 curriculum is obtained. This study are expected to serve as a guideline for developing Indonesian teaching materials that are more effective and relevant.